The Construction of History Learning Oriented to Gender Equality - Chaerunissa, Yasmin Nindya (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2017)
Gender issues have become a global agenda nowadays, where the inequality can make one of the parties, which in this case is women, discredited. Education, included history education of course, should be as one of the agents that can contribute to solve of gender problems. Based on social reconstruction philosophy, history education does not only talk about the past, but also relate to the present, and see the future. In this context, the history learning is made to be oriented in gender equality. The research location is on SMA Negeri 5 Bandung, class of social science. There are three main results in this research. First, to create a history learning that oriented to gender equality, the most important thing is that the teacher should have a deep understanding about it. It is fine whether the teacher is a man or woman, because gender equality is not only for woman, but for making a more equitable social order. History learning which oriented on gender equality could be delivered by its process and content. Second, on its implementation, history learning that could accommodate gender equality’s values is contextual learning. Teacher should be clever enough to make connection between the past and the present. It should be done dialogically. Discussion might be made through question and answer which bridged with gender issues emancipatory critical questions. It could help the students shape their own thought and direct which values that suit into them. Third, through this kind of construction, it resulted that students’ perception about gender equality developed. The students placed basically man and woman is in an equal partnership, where any kind of chances are open equally for both. It happened also friction about domestic role is not only for woman again, but as shared responsibility. Concluded, history learning could contribute in cultivating of gender equality, as a part to develop the social justice.